A Transnational Faith: El Salvador and Immigrant Christianity - Danielson, Robert A. (The Asbury journal, 2011)
Immigration is radically shaping the makeup of the United States; however immigration today is radically different than in previous generations. Modern immigration is characterized by transnationalism, where more immigrants are maintaining connections with their homelands. These connections have both positive and negative impacts on both the United States and the immigrant's countries of origin. El Salvador is one example of this trend. Financial remittances and gangs are representative of the way transnational migration affects a country of origin, like El Salvador, as well as the United States. The Church needs to adapt to this global trend and recognize its impact for mission and church growth in our time. Two indigenous churches in El Salvador demonstrate how the global church has spread beyond national borders through the impact of transnational migrants.